2010
DOI: 10.1177/0886260510368161
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence Perpetration and Victimization Among South Korean College Students: A Focus on Gender and Childhood Maltreatment

Abstract: Unlike the attention given to intimate partner violence among adolescents and young adults in western societies, dating violence is not currently recognized in South Korea as a social phenomenon in terms of research, prevention, and intervention. Childhood maltreatment has been identified in previous research as a risk factor for violence in a later dating relationship. This study examines the relationship between childhood maltreatment and physical and psychological dating violence perpetration and victimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 66 publications
9
23
0
9
Order By: Relevance
“…Moreover, in university students from Kyrgyzstan physical partner violence victimization was significantly higher in women than men, and in Thailand sexual partner violence victimization was significantly higher in male than in female students. These findings are in concordance with previous studies indicating similar proportions of IPV between females and males, and a preponderance of female gender IPV victimization, especially sexual violence victimization 16,20,24,25 . This study found that being in a higher study year at university was associated with a higher prevalence of IPV, which may be explained by the possibility that at older ages more sexual partnerships are engaged into than at younger ages or earlier study years.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, in university students from Kyrgyzstan physical partner violence victimization was significantly higher in women than men, and in Thailand sexual partner violence victimization was significantly higher in male than in female students. These findings are in concordance with previous studies indicating similar proportions of IPV between females and males, and a preponderance of female gender IPV victimization, especially sexual violence victimization 16,20,24,25 . This study found that being in a higher study year at university was associated with a higher prevalence of IPV, which may be explained by the possibility that at older ages more sexual partnerships are engaged into than at younger ages or earlier study years.…”
Section: Discussionsupporting
confidence: 83%
“…In terms of risk factors, this study found in multivariate logistic regression analyses, in agreement with a number of studies 14,[16][17][18][24][25][26][27][28][29][30][31] , that having experienced childhood physical and sexual abuse, tobacco use, alcohol use in the context of sex, PTSD symptoms and depression symptoms were associated with IPV. In addition, sexual risk behaviour (having had two or more sexual partners in the past year) and having a history of an STI in bivariate analysis was found to be associated with IPV.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…6 Başka bir çalışmanın sonuçları ile uyumlu olarak çalışma-mızda çocukluk döneminde fiziksel şiddete uğra-yanlarda uğramayanlara göre flört şiddeti anlamlı oranda daha yüksek bulunmuş, ancak flört şiddeti açısından bir risk etkeni olarak göste-rilememiştir. 15 Sigara içenlerde şiddete uğrama ve şiddet uygulamanın, sigara içmeyenlere göre daha yüksek olduğunu bildiren çalışmaların aksine, çalışmamızda sigara ve alkol kullanan öğren-cilerde kullanmayanlara göre flört şiddetine uğrama açısından anlamlı farklılık bulunmamış-tır. 16,17 Bir gözden geçirme çalışmasında depresif bozukluk, anksiyete bozukluğu ve travma sonrası stres bozukluğu olan kadınlarda ruhsal bozukluğu olmayanlara göre flört şiddetinin daha yüksek olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…An individual who was exposed to violence as a child tends to view violent behavior in a relationship as acceptable (Oliveira & Sani, 2009;Gover, Park, Tomsich, & Jennings, 2011).…”
Section: Introductionmentioning
confidence: 99%